NURSES’ KNOWLEDGE, ATTITUDES AND PRACTICES REGARDING DIABETIC FOOT ULCERS - SADIQULLAH, .; SADDIQUE , H; JABEEN, R (Biological and Clinical Sciences Research Journal, 2024)
Diabetic foot ulcers (DFUs) are a major complication of diabetes, contributing significantly to morbidity and healthcare costs. Nurses play a critical role in the prevention and management of DFUs. This study aimed to assess the knowledge, attitudes, and practices of nurses regarding diabetic foot care in a tertiary care hospital in Pakistan. Methods: A descriptive cross-sectional study was conducted among 124 nurses working in medical and surgical wards of a tertiary care hospital in Lahore, Pakistan. Participants were recruited using convenience sampling. Data were collected through a validated structured questionnaire assessing demographic characteristics, knowledge, attitudes, and practices. Statistical analysis, including descriptive and inferential statistics, was performed using SPSS version 26. Results: The study revealed moderate levels of knowledge, with 44.4% of nurses correctly identifying neuropathy as a primary factor for DFUs. However, only 35.5% recognized sensory neuropathy as a cause of unnoticed skin damage, highlighting knowledge gaps. Attitudes toward diabetic foot care were generally positive, but 24.2% agreed that regular assessment of DFUs is unnecessary. Practices were suboptimal, with only 36.7% of nurses consistently maintaining proper patient positioning and 40% regularly monitoring foot conditions. Education and professional experience were significantly associated with better knowledge and practices (p < 0.05). Conclusion: While nurses demonstrated moderate knowledge and positive attitudes, significant gaps in practices and specific knowledge areas were identified. Structured training programs, regular competency assessments, and policy interventions are essential to improve nursing competencies and patient outcomes in diabetic foot care.